Aerodynamic performance of a quadcopter rotor in crossflow conditions (2021)
A computational study of the aerodynamic performance of a quadcopter rotor in crossflow conditions with variations in attack angle was conducted. A simulation methodology was proposed and carried out in order to predict the aerodynamic performance of the rotor through a set of twelve different conditions that presented variations in its attack angle and advance ratio. A description of the thrust, power, drag and roll moment coefficients is presented for all studied conditions. It was found that the thrust generated by the rotor tends to decrease linearly with the increase in attack angle, decreasing faster with the increase in advance ratio. A similar trend was found for the torque generated by the rotor and the roll moment on the rotor, as they too decrease linearly with the increase of the attack angle. It was found that the drag on the rotor behaves in a manner consistent with the behavior of a typical airfoil, staying near constant at small attack angles and increasing exponentially thereafter. A study of the wake was conducted, and it was determined that the separation of the wing tip vortices could be the cause of the decrease in thrust and power as the rotor is operated at higher advance ratios and attack angles. Finally, through the aerodynamic performance predicted by the study, several recommendations were made in terms of the design and operation of the rotor in question.